SOMEBODY TO BLAME: ON THE CONSTRUCTION OF THE OTHER IN THE CONTEXT OF THE COVID-19 OUTBREAK - MORENO BARRENECHE, SEBASTIÁN (Society Register, 2020)
Besides the impact that COVID-19 has had in the sanitary, political and economic domains, it has also triggered multiple discursive processes, what opens up the field for an analysis from sociosemiotics, the social science interested in the study of ‘meaning in action’. The aim of this article is to discuss from such a perspective how the current crisis linked to the COVID-19 virus has given place to the emergence of processes of narrative construction of an ‘Other’ to be blamed for the threat. While in some contexts the dominant narrative has been that COVID-19 is ‘the Chinese’ –and their unhealthy culinary habits– fault, in others the focus has been set on ‘the irresponsible’ that do not stay home when indicated to do so, as well as on ‘the posh’, given that they can afford travelling and hence can import the virus on their return. Departing from the premise which poses that cognition is articulated in narrative terms, the article argues how, in cases such as the current COVID-19 crisis, a discursive construction of collective actors by means of mechanisms of actorialization, generalization and axiologization is necessary for the dynamics of blame-attribution.